Analysis of Factors Affecting the Achievement of Long Jump Skills of Students of SD Negeri 05 Kikim Timur - Fahlifi, Rizal; Kristina, Putri Cicilia; Putri, Siti Ayu Risma (Journal of Social Work and Science Education, 2023)
This study aims to analyze the factors that influence the long jump achievement of Elementary School 05 Kikim Timur students. This study uses a quantitative approach with an ex-post facto research design. This research was conducted at Elementary School 05 Kikim Timur. The sample used was 22 grade 5 students. Data collection techniques used a scale. The data analysis technique uses the normality test. Test the hypothesis using the t-test, and statistical hypothesis using t-test. Based on hypothesis testing with the Independent Sample t-Test at speed t count 3.742 > t table 1.682, agility t count 4.253 > t table 1.682, and power t count 4.321 > t table 1.682. The conclusion from the research conducted was that the average gross motor skills of grade 5 students at SD Negeri 5 Kikim Timur using the traditional long jump game were better. So that traditional games have an influence on students’ gross motor skills.